The Relationship Between Nurses’ Knowledge Level and the Timeliness of Emergency Management in Emergency Patients - Andi Agustang; Sarifudin Andi Latif (Jurnal Ilmu Kesehatan Nusantara, 2025)
Background: Timely emergency management is essential for preventing complications, disability, and mortality among emergency patients. Nurses’ knowledge influences their ability to assess patients, determine triage priorities, recognize life-threatening conditions, and provide appropriate interventions without delay. Research Objective: This study aimed to determine the relationship between nurses’ knowledge level and the timeliness of emergency management at the Emergency Department of Sinjai Regional General Hospital. Methods: This quantitative study employed an analytical observational design with a cross-sectional approach. The study was conducted in 2024 and involved all 21 nurses working in the Emergency Department, selected using total sampling. Data were collected using a structured knowledge questionnaire and an emergency-management timeliness observation sheet. Univariate analysis was performed using frequencies and percentages, while bivariate analysis used Fisher’s exact test with a significance level of 0.05. Results: Of the 21 nurses, 11 (52.4%) had good knowledge, six (28.6%) had moderate knowledge, and four (19.0%) had poor knowledge. Fourteen nurses (66.7%) provided timely emergency management, while seven (33.3%) did not. Fisher’s exact test showed a significant relationship between nurses’ knowledge and management timeliness (p = 0.024). Conclusion: Nurses with good knowledge were more likely to provide timely emergency management. Continuous training, clinical simulation, competency evaluation, and response-time monitoring are recommended to improve emergency care quality and patient safety.